2015
DOI: 10.1111/cup.12620
|View full text |Cite
|
Sign up to set email alerts
|

The many masks of cutaneous Lyme disease

Abstract: Early cutaneous Lyme disease, erythema migrans, may show different histopathologic patterns. The intent of this case series is to raise awareness of these findings to prevent misdiagnosis and keep this entity in the differential. Erythema migrans develops after a tick bite and subsequent infection with the spirochete, Borrelia burgdorferi. It most commonly manifests as a solitary, annular lesion with a bull's-eye appearance. Classic histopathologic findings include superficial and deep perivascular and interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Clinical symptoms in LB are not always specific, and LB can look like several diseases. 23 It can cause multisystem disease, particularly affecting the skin, musculoskeletal system, nervous system and heart. Lyme arthritis is usually not painful and is not accompanied by fever.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms in LB are not always specific, and LB can look like several diseases. 23 It can cause multisystem disease, particularly affecting the skin, musculoskeletal system, nervous system and heart. Lyme arthritis is usually not painful and is not accompanied by fever.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic features of Lyme disease often include a superficial and deep perivascular and interstitial infiltrate consisting of lymphocytes and plasma cells, and may include eosinophils and neutrophils; however, a variety of histopathologic patterns have been described and often suggest a broad histopathologic differential diagnosis. 6 , 7 The testing options for early-stage Lyme disease (<30 days since symptom onset) include polymerase chain reaction, enzyme-linked immunosorbent assay (ELISA), and Western blot ( Table I ). 8 The Center for Disease Control and Prevention currently recommends a 2-tier approach, involving an initial serum enzyme immunoassay, followed by IgG and IgM Western blotting or a secondary enzyme immunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, Wilson et al 8 described 4 patients with serologically confirmed erythema migrans whose biopsies from the periphery of their lesions lacked plasma cells; in a recent case series of 8 serologically confirmed patients with erythema migrans who underwent biopsy, 3 lacked plasma cells. 16 With the recent advancement of molecular techniques, one would think that the dermatopathologist would be able to confirm the diagnosis of erythema migrans readily on histologic sections. However, a recent review 17 highlights the impracticality of such endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, Wilson et al 8 described 4 patients with serologically confirmed erythema migrans whose biopsies from the periphery of their lesions lacked plasma cells; in a recent case series of 8 serologically confirmed patients with erythema migrans who underwent biopsy, 3 lacked plasma cells. 16…”
Section: Discussionmentioning
confidence: 99%